GURFAP: A Platform for Gene Function Analysis in Glycyrrhiza Uralensis - Yang, Jiaotong; Yan, Hengyu; Liu, Yue; Da, Lingling; Xiao, Qiaoqiao; Xu, Wenying; Su, Zhen (Frontiers in Genetics, 2022)
Glycyrrhiza uralensis (Licorice), which belongs to Leguminosae, is famous for the function of pharmacologic action and natural sweetener with its dried roots and rhizomes. In recent years, the whole-genome sequence of G. uralensis has been completed, which will help to predict gene regulation relationships and thus mine gene function for the further research. Here, we integrated the available genomic and transcriptomic of G. uralensis and constructed the G. uralensis gene co-expression network, then we annotated gene function of G. uralensis via aligning with public databases. Furthermore, gene families of G. uralensis were predicted by tools including iTAK, HMMER, InParanoid and PfamScan. Finally, we constructed a platform for gene function analysis in G. uralensis (GURFAP, www.gzybioinfoormatics.cn/GURFAP) and introduced various tools including BLAST, GSEA, Motif, Heatmap and Jbrowse for the analysis and prediction of gene function. In addition, our analysis based on this platform indicated that the biosynthesis of glycyrrhizin might be regulated by transcription factors MYB and bHLH. We also took the CYP88D6 gene in the synthesis pathway of glycyrrhizin as an example to demonstrate the reliability and availability of our platform. Our platform GURFAP may provide convenience for researchers to mine the gene function of G. uralensis and thus discover more key genes involved in the biosynthetic pathway of active ingredients.